Mechanical Evaluation Of Locking Compression Plate - Tong, Wen Le (Universiti Sains Malaysia, 2018)
Locking Compression Plate, LCP has been widely used in the femoral shaft fracture fixation. The clinical cases show that the failure of locking compression plate is possible before the adequate healing of the fracture. The types of failures occur are plate bending, plate breakage, bone failure at the screw and screw pulling out.This research is focus on determining the deformation in y-direction, maximum principal strain, minimum principal strain and strain in y-direction of locking compression plate surface using Digital Image Correlation and Finite Element Analysis. The results of two methods is compared to determine the accuracy of Digital Image Correlation method. Relative error will be calculated to determine the accuracy of Digital Image Correlation results. Besides, Finite Element Analysis is used to analyse the stress distribution of transverse fracture femoral shaft to determine the stress distribution at bone screw interface. The relative errors between Digital Image Correlation and Finite Element Analysis results are less than 15%, meaning that Digital Image Correlation is applicable to determining deformation and strain distribution of locking compression plate surface. Besides, the Finite Element Analysis shows that the stress distribution at first screw and second screw bone interfaces are 43.1 MPa and 77.5 MPa while the stress at other region of the bone is 2.9 MPa.